Transformation of surface water and groundwater and water balance in the agricultural irrigation area of the Manas River Basin, China - Guang, Yang; Xinlin, He; Xiaolong, Li; Aihua, Long; Lianqing, Xue (International Journal of Agricultural and Biological Engineering, 2017)
Calculation of the water balance is very important to relieve the pressure on water resources in arid agricultural irrigation areas. This research focused on irrigation water balance calculations in the Manas River Basin of the southern margin of the Junggar Basin of China, and aimed to analyze the groundwater level dynamic trend and response characteristics of the basin water cycle under water-saving irrigation measures. The surface water and groundwater coupling model of MIKE 11-Visual MODFLOW was used to simulate rainfall runoff in mountainous areas, and quantify the contribution of water balance components in the plain irrigation area. Convergence of the delayed watershed in the mountain area was obvious, and when the river runoff exceeded 200 m3/s, the error in the runoff simulation was large. The water balance in the plain agricultural irrigation area was in a negative equilibrium state, and the difference between recharge and discharge was −2.65 billion m3. The evapotranspiration was 24.49 billion m3 under drip irrigation, accounting for only approximately 51% of the total discharge. The lateral discharge of the unsaturated and saturated aquifers was 15.38 billion m3, accounting for approximately 32% of the total discharge. The main reason for the groundwater decline in the irrigation area was closely related to the extraction of groundwater, because the amount of recharge and discharge in the natural state was approximately identical. The MIKE 11-Visual MODFLOW model produced accurate results, and the research method provided a new exploration technique to quantify the effect of water supply mode on the groundwater table. The model is suitable for the management of water resources in arid areas. Keywords: water balance, coupling model, surface water and groundwater, water saving irrigation, Manas River Basin DOI: 10.25165/j.ijabe.20171004.3461 Citation: Yang G, He X L, Li X L, Long A H, Xue L Q. Transformation of surface water and groundwater and water balance in the agricultural irrigation area of the Manas River Basin, China. Int J Agric & Biol Eng, 2017; 10(4): 107–118.